Acute Symptoms of Mild to Moderate COVID-19 Are Highly Heterogeneous Across Individuals and Over Time. (1st March 2021) - Rodebaugh, Thomas L; Frumkin, Madelyn R; Reiersen, Angela M; Lenze, Eric J; Avidan, Michael S; Miller, J Philip; Piccirillo, Jay F; Zorumski, Charles F; Mattar, Caline
Abstract: Background: The symptoms of coronavirus disease 2019 (COVID-19) appear to be heterogenous, and the typical course of these symptoms is unknown. Our objectives were to characterize the common trajectories of COVID-19 symptoms and to assess how symptom course predicts other symptom changes as well as clinical deterioration. Methods: One hundred sixty-two participants with acute COVID-19 responded to surveys up to 31 times for up to 17 days. Several statistical methods were used to characterize the temporal dynamics of these symptoms. Because 9 participants showed clinical deterioration, we explored whether these participants showed any differences in symptom profiles. Results: Trajectories varied greatly between individuals, with many having persistently severe symptoms or developing new symptoms several days after being diagnosed. A typical trajectory was for a symptom to improve at a decremental rate, with most symptoms still persisting to some degree at the end of the reporting period. The pattern of symptoms over time suggested a fluctuating course for many patients. Participants who showed clinical deterioration were more likely to present with higher reports of severity of cough and diarrhea. Conclusions: The course of symptoms during the initial weeks of COVID-19 is highly heterogeneous and is neither predictable nor easily characterized using typical survey methods. This has implications for clinical care and early-treatment clinical trials. Additional research is needed to determine whether the decelerating improvement pattern seen in our data is related to the phenomenon of patients reporting long-term symptoms and whether higher symptoms of diarrhea in early illness presages deterioration. Graphical Abstract: